The Effect of Strength Differential on Material Effort and Lifetime of Steam Turbine Rotors Under Thermo-Mechanical Load - BANASZKIEWICZ, Mariusz; DUDDA, Waldemar; BADUR, Janusz (Engineering Transactions, 2019)
The paper presents the results of experimental tests and numerical simulations related with the strength differential effect. Tensile and compression tests on 2CrMoV low-alloy steel are performed to evaluate the magnitude of the yield stress difference in tension and compression. The strength differential parameter is then used in the formula for equivalent stress proposed by Burzynski. The material effort calculated using Burzynski and Huber-Mises-Hencky hypotheses was compared for different start-stop cycles. Analytical notch stress-strain correction rules by Neuber and Glinka-Molski were applied to compute elastic-plastic strain amplitudes in rotor circumferential grooves. It was finally shown that the strength differential effect has significant influence on the predicted fatigue life under thermo-mechanical loading.